DESULFURIZATION OF DISLE ISFAHAN OIL REFINERY COMPANY BY POLYDIMETHYLSILOXANE, POLY ETHYLENE GLYCOL, POLYETHERSULFONE AND POLY ACRYL NITRILE NANOCOMPOSITES: Life Sciences-Chemistry - MOHSEN FARSI; AMIR HEIDARINASAB; BIZHAN HONARVAR; MEHDI ARJMAND (International Journal of Life Science and Pharma Research, 2022)
In this research for fabricated the composite membranes usage a blend of polymers that are comprised of PDMS (polydimethylsiloxane), PEG (poly ethylene glycol), PES (polyether sulfone) and PAN (poly acryl nitrile) with crosslinking TMOS (tetramethyl orthosilicate) as crosslinking agent for decrease sulphur of diesel Isfahan oil Refinery company. Total sulphur of diesel as feed to membrane module is 6380ppm. In the research, four kinds of membrane including PDMS, blend of PDMS with PEG, blend of PDMS with PES and blend of PDMS with PAN are used. The process variables in this research are pump pressure of membrane module (5-9 Bar), crosslinking agent consumption (1.5 and 3 wt. %), crosslinking temperature (65-85ċ) and crosslinking time (0.5-2.5 hours). According to the research, it is observed that by increasing pump pressure, crosslinking agent consumption and crosslinking temperature, the sulfur content of retentate stream decreases if other variables remain constant. However, the conditions are different for the crosslinking time; when crosslinking time increases from 0.5 hours to 1.5 hour, the sulfur content of retentate stream decreases but when the time increases to 1.5 hours and other variables remain constant, sulfur content increases.